2022
DOI: 10.1055/s-0042-1759795
|View full text |Cite
|
Sign up to set email alerts
|

Free Flap Donor-Site Complications and Management

Abstract: Free flap harvest will occasionally result in donor-site complications and morbidity. Most of these complications are managed simply without producing lingering effects on activities of daily living. However, some patients will sustain limb weakness, gait issues, chronic pain, and nonhealing wounds. Frank preoperative discussion between surgeon and patient is essential to maximize postoperative outcome and manage expectations. Fastidious surgical technique will help minimize the risks of hematoma, seroma, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(65 reference statements)
0
2
0
1
Order By: Relevance
“…Neben den zuvor beschriebenen möglichen Hypästhesien und Krafteinschränkungen kommt es hier häufig zu Hämatomen, Seromen oder Wundheilungsstörungen mit Dehiszenzen, Nekrosen der transplantierten Haut und in der Folge freiliegenden Sehnen. Der Verschluss des Hebedefekts mittels Hauttransplantat ergibt in diesem motorisch im Alltag häufig beanspruchten Gebiet nicht immer ein ästhetisch und funktionell zufriedenstellendes Ergebnis [13,14].…”
Section: Caveunclassified
“…Neben den zuvor beschriebenen möglichen Hypästhesien und Krafteinschränkungen kommt es hier häufig zu Hämatomen, Seromen oder Wundheilungsstörungen mit Dehiszenzen, Nekrosen der transplantierten Haut und in der Folge freiliegenden Sehnen. Der Verschluss des Hebedefekts mittels Hauttransplantat ergibt in diesem motorisch im Alltag häufig beanspruchten Gebiet nicht immer ein ästhetisch und funktionell zufriedenstellendes Ergebnis [13,14].…”
Section: Caveunclassified
“…Closed incision negative pressure therapy (ciNPT) is a potential alternative to conventional dressings for management of free flap donor sites. 1 , 2 Although traditionally applied to open wounds, negative-pressure wound therapy has been used in management of surgical wounds and has been associated with a decreased risk of surgical site infection. 3 , 4 Negative-pressure wound therapy accelerates wound healing through promotion of blood flow, expression of growth factors, and removing excess fluid while maintaining a closed environment that holds the wound edges together.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition is supplied to the flap through microvascular anastomosis surgery and vascular anastomosis in the recipient area. The advantages of free flap reconstruction include selection of well-matched tissue, shape plasticity and reliable vascularity (3). Although free flap surgery in children is challenging, several studies have shown the same or even higher success rates as in adults (4,5).…”
Section: Introductionmentioning
confidence: 99%